An experimental investigation of the influence of website emotional design features on trust in unfamiliar online vendors. (February 2017) - Pengnate, Supavich (Fone); Sarathy, Rathindra
Abstract: Online trust is considered as a critical factor in online shopping, especially when dealing with unfamiliar vendors. This research provides empirical findings from an experimental investigation of the influence of website emotional design features, visual appeal and ease of use on users' perceptions of usefulness, trust, as well as intention to use websites. The proposed research model was developed based on theories in the human-computer interaction and Information Systems domains. An experiment was conducted using a hypothetical website with four conditions of treatment manipulation. The study revealed that visual appeal can produce a greater influence on customers' evaluation of trust, than ease of use. It was also found that both visual appeal and ease of use are contributing factors in developing online trust among male customers, with visual appeal dominating trust formation among female customers. Highlights: Empirical study examining effects of web features on trust in unfamiliar vendors. Combining theories from both the HCI and IS domains. Visual appeal is an important determinant of trust in the unfamiliar vendor context. Gender effect: Visual appeal is more important to female than male in forming trust. The results are different from prior studies that dealt primarily with familiar websites.